How to Carry Out a Democratic Ethnobotanical Study - Carlessi, Pedro Crepaldi (Ethnobiology Letters, 2019)
This contribution aims to share some experiences and methodological considerations that arose during an ethnobotanical research project with an Afro-Brazilian religious community in the city of São Paulo, Brazil. By presenting ontological features of plants used in religious practices, and the ways relations are created within this religious cosmology, this work opens a discussion about the political commitments of doing contemporary ethnobotanical science. When the ways of being and living in communities considered “traditional”—here referring to Afro-Brazilian religious communities, and specifically to the Umbanda Afro-Brazilian religion—are treated as equally valid, questions arise about the reaches of our own scientific practices, creating possibilities to construct practices and policies that preserve these communities’ vitality in the face of the overwhelming imposition of colonialism. In this sense, ethnobotanical research is at an analytical crossroads that can give the field an advantage over the political paralysis of the sciences and over the clandestine politicization of science as the spokesperson for a singular nature. These considerations lead to self-reflection on scientific expertise and democratic ways of producing knowledge about plants in plural cultural contexts.